Letˋs Pay Attention to Covid and Move Forward - T. , Avramov (Clinical Medicine And Health Research Journal, 2023)
Introduction: Zoonoses are diseases transmitted from animals to humans and pose a major threat to human health and life. Animals are often asymptomatic carriers of pathogens and spread them in the environment with their excreta. Their course varies from the common cold to more severe and often fatal diseases in humans. Before the COVID-19 infection caused the global pandemic in 2020, coronavirus diseases were primarily of veterinary interest. The COVID-19 pandemic has changed the way we live and strained healthcare systems around the world. This pandemic has necessitated the development of protective and therapeutic measures against the spread of SARS-CoV-2. The lack of optimal vaccine against SARS-CoV-2 offering long-lasting protection against the different viral variants, as well as a drug, allowing the treatment of all variants of COVID-19 directed us to the use of dietary components and agents that are applicable in the context of competitive inhibition by blocking part of the receptors to protect against coronavirus-related diseases. Discussion: Lactobacillus and carrageenans may have a protective effect against SARS-CoV-2 infection alone or in combination in healthy subjects. Reducing the viral load in the nasopharynx may drastically reduce the risk of transmission of COVID-19. Infectious diseases are among the strongest types of selective pressure driving human evolution. Genetics in the coming decades will likely allow us to understand the dynamics of human immune system formation. By learning from our mistakes and successes, we will be able to more successfully deal with the challenges posed by zoonoses in the future.